1983
DOI: 10.1164/arrd.1983.127.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Oxygen Administration and Prognosis in Chronic Obstuctive Pulmonary Disease and Cor Pulmonale1–3

Abstract: The purpose of this study was to develop criteria for predicting survival and clinical improvement with long-term domiciliary home oxygen therapy (LTDO2) in patients with both chronic obstructive pulmonary disease (COPD) and cor pulmonale (CP). Twenty-eight such patients were divided into 2 groups, responders (R) and nonresponders (NR), on the basis of the fall in their mean pulmonary artery pressure (delta PAP) while breathing 28% O2 for 24 h. The R(n = 17) and NR (n = 11) had delta PAP greater than and lesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(41 citation statements)
references
References 12 publications
0
40
0
1
Order By: Relevance
“…First, studies performed in COPD patients have shown not only a wide variation in the individual responses of the pulmonary circulation to changes in inspired oxygen concentration [14,33,34], but also a low correlation between Pa,O 2 and Ppa [7]. Second, LTOT does not reverse pulmonary hypertension, although it prevents its progression [35].…”
Section: Mechanisms Of Pulmonary Vascular Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, studies performed in COPD patients have shown not only a wide variation in the individual responses of the pulmonary circulation to changes in inspired oxygen concentration [14,33,34], but also a low correlation between Pa,O 2 and Ppa [7]. Second, LTOT does not reverse pulmonary hypertension, although it prevents its progression [35].…”
Section: Mechanisms Of Pulmonary Vascular Changesmentioning
confidence: 99%
“…At this stage, the reactivity of pulmonary arteries to hypoxia might also be altered in some patients with mild COPD [16,34,41], hence contributing to alveolar ventilation/perfusion ratio (V9A/Q9) mismatching and promoting the development of arterial hypoxaemia. In this scenario, sustained exposure to hypoxaemia may induce further pulmonary vascular remodelling thus amplifying the initial effects of cigarette-smoke products ( fig.…”
Section: Mechanisms Of Pulmonary Vascular Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings supporting this circumstance can be listed as follows: 1) non-normalization of PAP with oxygen therapy [51] and variability of the hemodynamic response to oxygen therapy [52], 2) the relationship between PAP and oxygen partial pressure (PaO 2 ) is not strong and cannot always be shown [3,10]) changes in pulmonary vasculature and detection of endothelial dysfunction in non-hypoxic mild COPDs [39,53,54] and 4) observation of PAP increase in animal models exposed to cigarette smoke before COPD [55]. As a result, hypoxia plays a key role in the development of PHT in this patient group, but it cannot be held responsible alone for all hemodynamic changes.…”
Section: Hypoxiamentioning
confidence: 97%
“…These changes in intrathoracic pressure cause lowered cardiac output due to decreased systemic venous return or increase in afterload [28]. Therefore, in advanced COPD patients with mild PHT (25-30 mmHg) at rest, there is a significant increase in PAP (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) with an increase in cardiac output after constant moderate level exercise. When clinically assessed, an exercise at this level can coincide with daily activities, and therefore, significant PHT can develop in daily activities [31].…”
Section: Exercisementioning
confidence: 99%